Anti-amyloid-β protein agents for the treatment of Alzheimer's disease: an update on emerging drugs - Lozupone, Madia; Solfrizzi, Vincenzo; D'Urso, Francesca; Di Gioia, Ilaria; Sardone, Rodolfo; Dibello, Vittorio; Stallone, Roberta; Liguori, Angelo; Ciritella, Chiara; Daniele, Antonio; Bellomo, Antonello; Seripa, Davide; et al. (Expert opinion on emerging drugs, 2020)
Currently available Alzheimer's disease (AD) therapeutics are only symptomatic, targeting cholinergic and glutamatergic neurotransmissions. Several putative disease-modifying drugs in late-stage clinical development target amyloid-β (Aβ) peptide and tau protein, the principal neurophatological hallmarks of the disease. Phase III randomized clinical trials of anti-Aβ drugs for AD treatment were searched in US and EU clinical trial registries and principal biomedical databases until May 2020. At present, compounds in Phase III clinical development for AD include four  anti-Ab monoclonal antibodies (solanezumab, gantenerumab, aducanumab, BAN2401), the combination of cromolyn sodium and ibuprofen (ALZT-OP1), and two small molecules (levetiracetam, GV-971). These drugs are mainly being tested in subjects during early AD phases or at preclinical stage of familial AD or even in asymptomatic subjects at high risk of developing AD. The actual results support the hypothesis that elevated Aβ represents an early stage in the AD continuum and demonstrate the feasibility of enrolling these high-risk participants in secondary prevention trials to slow cognitive decline during the AD preclinical stages. However, a series of clinical failures may question further development of Aβ-targeting drugs and the findings from current ongoing Phase III trials will hopefully give light to this critical issue.